Grosharpwetterlagen and precipitation trends in the Elbe river catchment - Peter Christian Werner; Friedrich-Wilhelm Gerstengarbe; Frank Wechsung (Meteorologische Zeitschrift, 2008)
Exemplified by the Elbe river catchment, this is a study on how far certain meteorological phenomena occur simultaneously in the entire area and what their causes are. The study is performed for days with/without precipitation for the 1951-2003 time period. It is demonstrated that the frequency of these events is increasing and closely linked to the development of certain Großwetterlagen. The most striking development can be observed in summer with an increase in the number of days without precipitation from 85 (1951/1980) to 123 (1974/2003). This growth is strongly connected with an increase of the high pressure patterns HM and BM from 422 up to 532 in the same time period. In winter the cases of days with precipitation triple (from 13 to 39) parallel to an increase of the cyclonal Großwetterlagen WZ and NWZ from 637 up to 806. A further result is the detection of the erratic nature of this development rather than it being a continuous trend.